Students' Conceptual Understanding of Alternative Energy Material After RADEC Model Learning in Grade IV Elementary School - Sumia, Aam; Sopandi, Wahyu; Somantri, Mubarok (International Conference on Elementary Education, 2025)
The importance of understanding the concept of alternative energy for elementary school students cannot be separated from the current global conditions. The RADEC learning model is a learning approach designed to improve students' understanding of concepts in different ways. The objectives of this study are 1) to determine the differences in students' learning outcomes in understanding the concept of alternative energy functions using the RADEC learning model in sixth grade. 2) To obtain a learning model that provides better learning outcomes in the subject of alternative energy functions in sixth grade elementary school. The research design used in this study is a quasi-experiment with a nonequivalent control group design. The population of this study was all sixth-grade elementary school students. The instruments used in this study included descriptive tests and observation sheets. The instruments used in this study were test questions adjusted to the revised Bloom's taxonomy understanding indicators. The results of data analysis showed that the RADEC learning model had a significant effect on improving students' conceptual understanding. Normality and homogeneity tests ensured that the data met the assumptions of parametric statistical analysis. The Paired Sample T-Test showed a significant increase in the pretest and posttest of both groups, with a greater increase in the experimental group. The Independent Sample T-Test revealed a significant difference between the two groups in the posttest (Sig. 0.003 < 0.05). The N-Gain analysis showed an average increase in understanding of 46.41% in the experimental group, higher than the control group at 30.15%. This study concluded that the RADEC model was more effective than the STEM method in improving students' understanding of alternative energy concepts.